CURRENT STATUS OF FISH PARASITES IN ARTIFICIAL PONDS IN KARAKALPAKSTAN (Intent Research Scientific Journal, 2023)
This article presents a thorough examination of fish parasites in artificial basins within the region of Karakolpogistan. The study aims to understand the current state of fish parasites, assess their prevalence, and discuss the potential implications for fish health and overall ecosystem balance. The research employs various methods, including sampling, laboratory analysis, and statistical tools, to yield valuable insights into the dynamics of fish parasites in these artificial habitats. The findings offer significant contributions to the field of aquatic parasitology and provide important considerations for the management of artificial basins.